Quantification of regional variations in glenoid trabecular bone architecture and mineralization using clinical computed tomography images. Issue 1 (26th June 2017) - Jun, Bong‐Jae; Vasanji, Amit; Ricchetti, Eric T.; Rodriguez, Eric; Subhas, Naveen; Li, Zong‐Ming; Iannotti, Joseph P.
ABSTRACT: The purpose of this study was to demonstrate feasibility of a clinical CT imaging and analysis technique to quantify regional variations in trabecular bone architecture and mineralization of glenoid bones. Specifically, our objective was to determine to what extent clinical CT imaging of intact upper extremities can describe variations of trabecular bone architectures at anatomic and peri‐implant regions by comparing trabecular bone architectures as measured by high‐resolution, micro CT imaging of same excised glenoid bones. Bone volume fraction (BVF), trabecular bone thickness (TbTh), number of trabecular bone (TbN), spacing (TbS), pattern factor (TbPf), bone surface area (BSA), and skeletal connectivity (Conn.), in addition to bone mineral content (BMC) and bone mineral density (BMD), were quantified from both clinical and micro CT images using whole bone, anatomic, and peri‐implant bone masks. Strong correlations of BVF, TbTh, TbSp, BMC, and BMD were found between clinical CT and micro CT imaging methods. The variations in BVF, TbTh, TbSp, TbN, BMC, and BMD at anatomical and peri‐implant regions were larger than those at whole bone regions. In this study, we have demonstrated that this clinical CT imaging methodology can be used to quantify variations of a patient's glenoid bone at anatomic and peri‐implant levels. Statement of Clinical Significance. An in vivo quantitative assessment of glenoid trabecular bone architecture in the anatomic and peri‐implant regions may improve our understanding on the role of bone quality on glenoid component loosening following total shoulder arthroplasty. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:85–96, 2018. Abstract : We demonstrated feasibility of clinical CT imaging and analysis technique to quantify regional variations in trabecular bone architecture and mineralization of glenoid bones. Strong correlations of bone volume fraction, trabecular thickness and spacing, bone mineral contents, and density were found between clinical CT and micro CT imaging. An in vivo quantitative assessment of glenoid trabecular bone architecture in the anatomic and peri‐implant regions may improve our understanding on the role of bone quality on glenoid component loosening following total shoulder arthroplasty.